Optimization of RNA Extraction from Dry Blood Spots for Nanostring Analysis. Issue 4 (3rd April 2023) - McFarlin, Brian K.; Sass, Tatum N.; Bridgeman, Elizabeth A.
Abstract: Dry blood spot (DBS) technology has been widely used since the 1960's for the detection of protein biomarkers associated with various disease states. In this manuscript we report a revised approach using DBS samples to extract total RNA for use in downstream multiplex RNA detection methodology (Nanostring). To accomplish this objective, we have used commercially available supplies, kits, and equipment to ensure that the procedure described in this report can be adopted by any laboratory. The methods described in this report allow for the extraction of high‐quality, total RNA from a minimal volume (∼200 µl) of DBS spots. The isolated RNA can be analyzed using a multiplex, Nanostring system to yield results for up to 800 RNA targets. Additional bioinformatics and pathway annotation can be conducted to determine changes in biological signaling pathways. © 2023 Wiley Periodicals LLC. Basic Protocol : RNA extraction from DBS for multiplex RNA nanostring analysis Support Protocol 1 : RNA extraction from PAXgene blood Support Protocol 2 : Concentration of DBS RNA